PENGABDIAN KEPADA MASYARAKAT DENGAN PENDATAAN TANAH WAKAF MELALUI KULIAH KERJA NYATA TEMATIK (KKN-T) DI DESA KASIMPAR KECAMATAN PETUNGKRIYONO KABUPATEN PEKALONGAN - Tiara Febrianti; Kania Najwa Nareswari; Nur Ilmiyah; Muhammad Safiq Faiz; Jihan Rifatul Aola; Galya Adisti; Tia Melinda Salsabilah; Nuha Lubaba; Dina Faradisa; Devita Afia Dewi; Khoirul Muttaqin; Muhammad Elman Nazid; Ulwi Albab (Saweu: Jurnal Pengabdian Kepada Masyarakat, 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is a curricular activity that integrates the Three Pillars of Higher Education (Tri Dharma Perguruan Tinggi), namely education, research, and community service. The 63rd KKN Program of UIN K.H. Abdurrahman Wahid Pekalongan, Group 23, was conducted in Kasimpar Village, Petungkriyono District, Pekalongan Regency, from October 13 to December 11, 2025. Kasimpar Village is characterized as an agrarian community, with the majority of residents working as agricultural laborers. During the implementation, Group 23 carried out various flagship and supporting programs based on the theme Ecotheology and Land Affairs, covering the fields of education, environment, social, religious, and health sectors. These programs aimed to increase community participation and empowerment while fostering students’ social awareness. Despite challenges related to time constraints, limited funding, and coordination with the community, most programs were successfully implemented and provided positive impacts for both students and the local community. This KKN activity contributed to enhancing environmental awareness, empowering women and children, and encouraging more independent and sustainable community development.